Utilization of Corncob Hydrolysate Enables 2,3-Butanediol Production in Enterobacter cholerae - Lizhou Ma; Jieming Wang; Rui Zhi; Lucian A. Lucia; Guohui Li; Yu Deng (BioResources, 2022)
2,3-Butanediol (2,3-BDO) is an important industrial diol that could function in various fields. Currently, there are many substrates used for 2,3-BDO biosynthesis, but studies using green carbon sources such as corncob hydrolysate as a substrate are lacking. As a widely distributed waste lignocellulose-derived substrate, corncob hydrolysate is nutrient-rich and cost-effective. The present study evaluated 2,3-BDO production via an Enterobacter cholerae strain using corncob hydrolysate as carbon source. Chemical component analysis showed that concentrated corncob hydrolysate contained 233 g/L total sugar and showed no inhibitory effect, but it was beneficial for 2,3-BDO synthesis. Optimization experiments for fermentation resulted in a titer of 47.23 g/L 2,3-BDO with a yield of 0.30 g/g and a productivity rate of 0.66 g/L•h. This study is expected to provide insights for large-scale bioproduction of bulk chemicals utilizing corncob hydrolysates.